2018
DOI: 10.1101/214973
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide Analysis of Insomnia (N=1,331,010) Identifies Novel Loci and Functional Pathways

Abstract: Insomnia is the second-most prevalent mental disorder, with no sufficient treatment available. Despite a substantial role of genetic factors, only a handful of genes have been implicated and insight into the associated neurobiological pathways remains limited. Here, we use an unprecedented large genetic association sample (N=1,331,010) to allow detection of a substantial number of genetic variants and gain insight into biological functions, cell types and tissues involved in insomnia complaints. We identify 20… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 66 publications
5
44
0
1
Order By: Relevance
“…The basal ganglia are a group of subcortical nuclei involved in a range of functions, including motor control, reward-based learning and working memory (Alexander et al, 1991). A recent genome-wide association study, combined with tissue-specific gene-set analyses, showed strong enrichment of insomnia risk genes across the basal ganglia (Jansen et al, 2018). Altered activity in basal ganglia structures has previously been associated with Insomnia Disorder.…”
Section: Reduced Fronto-subcortical Connectivity In Insomnia Disordermentioning
confidence: 99%
“…The basal ganglia are a group of subcortical nuclei involved in a range of functions, including motor control, reward-based learning and working memory (Alexander et al, 1991). A recent genome-wide association study, combined with tissue-specific gene-set analyses, showed strong enrichment of insomnia risk genes across the basal ganglia (Jansen et al, 2018). Altered activity in basal ganglia structures has previously been associated with Insomnia Disorder.…”
Section: Reduced Fronto-subcortical Connectivity In Insomnia Disordermentioning
confidence: 99%
“…The need to discover and dissect genetic associations at ever finer detail, and advances in the throughput of genotyping and sequencing technologies has driven rapid increases in the scale of genetic epidemiology studies. Studies incorporating millions of individuals with genotypes either directly observed or inferred at tens of millions of genetic variants are now becoming common [1][2][3] . Data of this scale has effectively outgrown the practical limits of firstgeneration GWAS data formats 4,5 and new tools for storage, computation, and analysis are required.…”
Section: Introductionmentioning
confidence: 99%
“…The strongest association signal was on chromosome 2 at SNPs within gene MEIS1, known for association with Restless Leg Syndrome and Insomnia (Table 1). [15][16][17][18] The other three genetic loci were rs188904275 in JAKMIP2 (p-value = 3.7×10 -8 ), rs184670665 near IMPG1 (p-value = 2.4×10 -10 ), and rs73586669 near OR4E1 (pvalue = 2.4×10 -8 ), with JAKMIP2 previously found to be associated with Body Mass Index (BMI) measurements and pulmonary diseases 19 . These novel loci were not previously associated with activity levels during sleep.…”
Section: Loci Associated With Sleep-activity Traits and Circadian Traitsmentioning
confidence: 99%
“…Five SNPs were associated with long sleep duration > 10 hours, among which rs74460673 at gene TMEM39B was previously found to be associated with BMI 21,22 and rs573982927 at MYO3B was associated with obesity traits 23,24 . Twenty seven SNPs were found to be associated with sleep start, including three SNPs at or near gene MEIS1 related to Restless Leg Syndrome and insomnia [15][16][17][18] and nineteen SNPs at gene BTBD9 also related to Restless Leg Syndrome 25 ( Supplementary Table S1). Sleep start is also associated with one SNP at gene CYP7B1 related to BMI, two SNPs near gene HSD17B12 related to BMI 21,26,27 , two SNPs near MIR129-2 also related to BMI 21,22 and Alzheimer's Disease 28 , and two SNPs near LOC101928944 related to schizophrenia 29,30 .…”
Section: Loci Associated With Sleep-activity Traits and Circadian Traitsmentioning
confidence: 99%